The Conjuncture Institute at Moscow - Kondratieff, N. D. (Quarterly Journal of Economics, 1925)
Journal Article The Conjuncture Institute at Moscow Get access N. D. Kondratieff N. D. Kondratieff Moscow, Russia Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 39, Issue 2, February 1925, Pages 320–324, https://doi.org/10.2307/1884878 Published: 01 February 1925